Pengaruh Pengembangan Karir, Pengalaman Kerja dan Motivasi terhadap Kualitas Kerja Karyawan - Septa Intiar; Eliagus Telaumbanua; Kudsi Holil; Pretty Failasufa Aziza; Mohammad Gifari Sono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Superior and quality human resources must always be managed and supported by the company to achieve the expected performance. Achieving goals based on human resource management will show how the company should obtain, develop, foster, and prosper employees. This study aims to determine the effect of career development, work experience and motivation on employee work quality. The current analysis uses a quantitative approach. The results of the study found that career development, work experience, and motivation are interrelated and have a significant influence on employee work quality.